The effect of internal control components on the organizational performance of Moroccan public organization: a theoretical exploration - MAAROUFI, Abdelkader; EL HAJI, Hajar (Revue du contrôle, de la comptabilité et de l’audit, 2022)
The performance of a public organization can be enhanced by various managerial processes. This notion depends on the effective and efficient use of financial and non-financial resources. In order to optimize the use of the resources entrusted to all the employees of an organization, various forms of control are put in place by the management and the board of directors, among these major controls are internal control. If the concept of "internal control" is widely disseminated and known in the private sphere, its understanding and application are still recent in public administrations. This article aims to present the components of internal control and to examine the effect of these on the organizational performance of the Moroccan public administration within the framework of the COSO. The impact of the internal control system as a whole, as well as the impact of the five components of the COSO. The first component of internal control is the control environment, the second component is risk assessment, control activities is the third component, information and communication is the fourth component, and the fifth component is monitoring. These components are analyzed individually. The research results show a positive relationship between elements of internal control and organizational performance. Through a documentary analysis, we find that the magnitude of the impact of this effect varies across different elements of the internal control system.